Scooby-Doo!. Frankencreepy [videorecording (Blu-Ray + DVD)] - Krieg, Jim (Hanna-Barbera Productions, 2014)
Velma discovers she's inherited her great-great-uncle Dr. Von Dinkenstein's cursed castle in the terrifying town of Transylvania, Pennsylvania. Just when the gang persuades Velma to go claim her inheritance, the ghost of Dinkenstein Castle blows up the Mystery Machine as a warning! Now the crew must spring back into action, but this time it's personal! Who's responsible for the Dinkenstein monster? What family secret has Velma been hiding?